3+-2x=y

Simple and best practice solution for 3+-2x=y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+-2x=y equation:


Simplifying
3 + -2x = y

Solving
3 + -2x = y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -2x = -3 + y

Combine like terms: 3 + -3 = 0
0 + -2x = -3 + y
-2x = -3 + y

Divide each side by '-2'.
x = 1.5 + -0.5y

Simplifying
x = 1.5 + -0.5y

See similar equations:

| 4/5y-2(y-4)=3y-15 | | r/9=7 | | y^3+2y^2=y+2 | | 87.6=8.8-0.2 | | 1(y)=1(-4x-6) | | 5d-4=4 | | x-3/3=4+x/4 | | 3(2x+5)=2(4x+5)+9 | | 5d-4= | | Y=x/3+12 | | 6x-5=-53 | | 1.1q-1.9-2.4q=-2.3q-3.4 | | x-3x+5x=1 | | 2/5+3x=-118/5 | | -1=x/7+1 | | 0.55x+0.05(18+x)=0.10(-41) | | -1(y)=-1(-4x-5) | | (3+2i)+(5-2i)=8 | | -(6x+8)+12=3x-20 | | 563=a-334 | | 1(y)=1(-4x+2) | | -4x+1=-7/5 | | 3((16)1/2) | | 80+6a=7a-145 | | X+47=183 | | 180.75=40+5*x | | (2x-1)*6=(4-x)*3 | | 157=x-987 | | -5(3x+5)-3=-5(x+3)+2x | | 7((16)-1/2) | | x+2(x+1)=24+(x+4) | | 4x+3x+2=9 |

Equations solver categories